Foliar anatomy of Malpighia mexicana (Malpighiaceae) - Bárcenas-López, Lorena Yeraldi; Montaño-Arias, Susana Adriana; López-Sandoval, José Antonio; González Huerta, Andrés; Rubí-Arriaga, Martín; Vargas Simón, Georgina (Instituto de Ecología, A.C., 2018)
Background and Aims: Malpighia mexicana is a native tree widely distributed in Mexico, which is cultivated in orchards or backyards of rural areas, and source of economic, timber, ornamental and medicinal resources. Studies on foliar anatomy of the genus Malpighia are scarce; characters such as the shape, length, width and pubescence of the leaf are used to classify its species. As a consequence, the objectives of this study were to escribe the anatomical characteristics of the leaf of M. mexicana and to determine the structural characters that are influenced by the environment, in order to contribute to the taxonomic and ecoanatomical knowledge of the genus Malpighia in Mexico.Methods: Three individuals with similar height and coverage were selected in three sites; a sample composed of 20 leaves was obtained; the leaves were fixed in FAA, washed with water and processed by conventional anatomy techniques, ending with inclusion and infiltration in paraffin. Paradermal and transverse cuts were made (15-20 μm), photographs were taken, and measurements were recorded with the image analyzer Leica LV 40.Key results: The leaves of M. mexicana in paradermal section present polygonal and rectangular cells, in some cases ovate-rectangular, linear and thick anticlinal walls are hypoestomatic with paracitic stomatal complexes and present epidermal appendages with single and branched unicellular trichomes. Transversely the leaves consist of a simple unistratified epidermis and bifacial mesophyll. The development of adaptation strategies was observed in both mesic and xeric environments.Conclusions: The anatomical characters that allow to differentiate M. mexicana are the disposition and type of trichomes and type of stomata. Foliar anatomy presented correlated traits both with mesic (dorsiventral leaf, intercellular spaces in the mesophyll, absence of sclerenchyma) and xeric environments (epidermis of large cells, higher concentration of stomata in the abaxial surface).